Implementing an Undergraduate, Team-Based, First Aid Education Course (International Journal of First Aid Education)
First aid (FA) skills, including Cardiopulmonary Resuscitation (CPR) are the foundation of first responder care. Best practice guidelines to educate FA trainees are lacking. The current structure of FA training programs is based on pedagogy, derived indirectly from hospital-based and Emergency Medical Services training models. Most FA training programs focus on educating the participant to function as the sole provider of care; however there may be instances when individuals providing FA find themselves suddenly engaged as functioning members of teams caring for an individual in need. Findings indicate that patients are safer and receive higher quality care when providers work as a highly effective team. As a result, teamwork training programs have been integrated into multiple health training programs. Teamwork training has been found to reduce medical errors, promote patient safety, enhance positive patient outcomes, and improve communication in a variety of medical settings; however the impact of team-based training in FA education is unknown. We describe the development of a semester long, undergraduate-level, FA educational course incorporating team-based training. Results of this project may impact the methods by which individuals receive FA education. Further investigation into the use of teamwork training as the foundation for FA training is indicated to determine the outcomes for the acutely ill and injured.